Microcontroller based disturbance detector / Aiman Zaidan - Zaidan, Aiman (2014)
This paper discussed on the development of a disturbance detector. This disturbance detector can helps to identify the types of disturbances such as voltage sag and voltage swell that occur in an electrical power system. The detector has been with LCD screen to perform the type power disturbance. The detector has been developed by combining the hardware and software. It involves the use of microcontroller for detection of disturbances with appropriate use of programming. The test verification has been conducted and it is proven that this simples devices can produce a promising result.